Dumbo - Sharpsteen, Ben.; Choir, Hall Johnson; Jim Carmichael; Musical; Noreen Gammill (USA Walt Disney Video, 2002)
The stork delivers a baby elephant to A Disney "classic" that actually is a classic, Dumbo should be part of your video collection whether or not you have children. The storytelling was never as lean as in Dumbo, the songs rarely as haunting (or just plain weird), the characters rarely so well defined. The film pits the "cold, cruel, heartless" world that can't accept abnormality against a plucky, and mute, hero. Jumbo Jr. (Dumbo is a mean-spirited nickname) is ostracized from the circus pack shortly after his delivery by the stork because of his big ears. His mother sticks up for him and is shackled. He's jeered by children (an insightful scene has one boy poking fun at Dumbo's ears, even though the youngster's ears are also ungainly), used by the circus folk, and demoted to appearing with the clowns. Only the decent Timothy Q. Mouse looks out for the little guy. Concerns about the un-PC "Jim Crow" crows, who mock Dumbo with the wonderful "When I See an Elephant Fly," should be moderated by remembering that the crows are the only social group in the film who act kindly to the little outcast. If you don't mist up during the "Baby Mine" scene, you may be legally pronounced dead
Mrs. Jumbo wishes for a baby, but when the stork finally delivers, the baby has a distinctive enhancement - gigantic ears.
Helen Aberson
Languages : English, French, Italian Subtitle : English
Keywords: Animation; Family; Drama